Meaninglessness in Psychotherapy: Clinical Challenges and Spiritual Resources - Buju, Smaranda (Acta Philosophica, 2020)
This study shows some of the difficulties concerning the issue of meaninglessness in life when moving from the philosophical register to the therapeutic one without abandoning any of the perspectives. We see that authors from different fields of study (philosophy, psychotherapy, psychiatry) have common opinions about the minimal conditions for a healthy approach of the meaninglessness as philosophical and/or therapeutic issue. Beyond reviewing recent psychological research that indicates the important steps taken in the empirical and therapeutic research of meaninglessness, we notice the challenge of therapists to combine resources from philosophy, psychology and religion. As religion is insufficiently developed in interventions oriented towards meaning and lack of meaning, we sustain integrating two theological virtues, faith and hope, as unconventional resources in support therapy to diminish the feeling of lack/loss of meaning in life.